Acid volatile sulfide and simultaneously extracted metals in superficial sediments from Baihua Lake, China - 章吉萍 胡继伟 黄先飞 沈威 金梅 付丽亚 靳小飞 (Chinese journal of oceanology and limnology, 2013)
The bioavailability of five divalent cationic heavy metals (Pb, Cd, Cu, Zn and Ni) in 10 superficial sediment samples from Baihua Lake was assessed based on the molar ratio of simultaneously extracted metals (SEMs) to acid volatile sulfide (AVS). Atomic absorption spectrometry (AAS) and X-ray powder diffraction (XRD) were used to determine the heavy metal concentrations and examine the mineralogy of the crystalline phases, respectively. The AVS loadings in sediments from Baihua Lake ranged from 64.30 to 350.08 μmol/g (dry weight). The corresponding SEM levels for the sampling sites varied from 1.770 to 14.660 μmol/g. The molar ratio of SEMs to AVS ranged from 0.014 to 0.084 with a mean value of 0.034. The XRD analysis also confirmed the presence of some metal sulfides in sediments from Baihua Lake. The SEMs/AVS ratios for all sampling sites were significantly lower than 1.0, indicating that AVS in the sediments was sufficient to bind the five heavy metals; thus, these heavy metals are currently not significantly bioavailable to benthic organisms. Comparing the SEMs results to published guideline values for metal toxicity to benthic organisms in sediments, however, suggests that Zn and Ni pose a risk at some sampling locations in Baihua Lake.